2012
DOI: 10.1590/s1808-86942012000400011
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de perda auditiva incapacitante em Juiz de Fora, Brasil

Abstract: Dat a on the prevalence of disabling hearing loss (DHL) in Brazil is scarce, which impacts healthcare professionals' knowledge on the extent of the problem. Objectives:This study aimed at estimating DHL prevalence in the municipality of Juiz de Fora, Minas Gerais, to identify individual-related variables and find risk areas. Materials and Methods:This was a descriptive sectional population study held from January to October of 2009. We randomly selected 349 households with 1,050 individuals who with ages rangi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0
10

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 30 publications
3
7
0
10
Order By: Relevance
“…The protocol "Ear and hearing disorders survey" proposed by the World Health Organization (WHO) performed an investigation on "ear pain" 34 but it is worth mentioning that the objective of the protocol was wider than only determining the prevalence of hearing loss. Besides, studies of this nature that have followed this protocol 13,33,35,36 did not present "ear pain/ache" in their results. Among school-age individuals, between the ages of 5 and 14 years old in India, one of the most common ear, nose and throat problem reported was earache, in 8.67% of the sample, 37 which was lower than what was presented herein.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The protocol "Ear and hearing disorders survey" proposed by the World Health Organization (WHO) performed an investigation on "ear pain" 34 but it is worth mentioning that the objective of the protocol was wider than only determining the prevalence of hearing loss. Besides, studies of this nature that have followed this protocol 13,33,35,36 did not present "ear pain/ache" in their results. Among school-age individuals, between the ages of 5 and 14 years old in India, one of the most common ear, nose and throat problem reported was earache, in 8.67% of the sample, 37 which was lower than what was presented herein.…”
Section: Discussionmentioning
confidence: 97%
“…Two studies that evaluated incapacitating hearing losses found prevalences of 7.1% 33 and 3.03%. 13 However, data presented herein could relate to these studies, as incapacitating loss does not include individuals with discrete and slight loss, for example. Such an inclusion would increase prevalence, such as the value of 16.84% found in the South region of the country, 32 similar to that presented herein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ainda com relação ao grau de perda auditiva, constatou-se que os idosos com idade mais elevada apresentavam maior grau de perda auditiva. Resultados semelhantes foram observados por estudos anteriores que salientam a progressão da perda auditiva com o aumento da idade (CARMO et al, 2008;MENESES et al, 2010;KIDD;HUMES, 2012;BARAKY et al, 2012).…”
Section: Discussionunclassified
“…Ao analisar a presença e o grau de perda auditiva e o sexo dos componentes da amostra, não foram observadas associações, em semelhança ao que foi relatado por Lasisi, Abiona e Gureje (2010), mas contrariamente ao que foi descrito por Carmo et al (2008), Sousa et al (2009) e Baraky et al (2012). Este fato pode ser atribuído às características dos indivíduos avaliados.…”
Section: Discussionunclassified